Longitudinal Assessment of Alterations in Peripheral Inflammatory Markers Over a Hospitalization Period in Patients with Schizophrenia - Süleyman Dönmezler; Oya Güçlü; İmren Kurt; Halil Ibrahim Ozturk (Genel Tıp Dergisi)
Objective: To assess the effects of regular medication administration, diet, sleep, and physical activity provided by hospital care on inflammatory markers in schizophrenia patients. The primary hypothesis of our study is that the assembly of various factors, will reduce low-grade inflammation in a short period. Materials and Methods: This retrospective longitudinal study involved 106 patients diagnosed with schizophrenia who met the exclusion and inclusion criteria. Inflammatory markers such as neutrophil-to-lymphocyte Ratios (NLR), monocyte-to-lymphocyte ratios (MLR), platelet-to-lymphocyte ratios (PLR), C-reactive protein-to-albumin ratios (CAR), and systemic immune inflammation indices (SII) were calculated at the time of hospital admission and after three weeks. Results: The mean age of the participants was 39.0±13.1 years and the majority were male (n: 75). Reductions were observed in all inflammatory markers after three weeks. The CRP decreased from a median value of 2.6 (interquartile range (IQR): 1.1-5.3) to 1.90 (IQR: 0.85-3.30) (p=0.001, effect size=0.375). The CAR changed from 0.064 (IQR: 0.026-0.115) to 0.043 (IQR: 0.017-0.077) (p=0.005, effect size=0.371). The NLR demonstrated a significant reduction from 2.31 (IQR: 1.73-3.24) to 1.73 (IQR: 1.28-2.27) (p<0.001, effect size=0.647). The SII decreased from 634 (IQR: 425-870) to 470 (IQR: 321-645) (p<0.001, effect size=0.577). The PLR went down from 9.85 (IQR: 7.4-12.7) to 8.21 (IQR: 6.22-10.3) (p<0.001, effect size=0.547). Lastly, the MLR reduced from 0.297 (IQR: 0.221-0.378) to 0.258 (IQR: 0.195-0.319) (p<0.001, effect size=0.522). Conclusion: This study underscores the influence of regular antipsychotic treatment and hospital care in reducing inflammation markers like NLR, MLR, PLR, SII, and CAR in schizophrenia patients. Future studies should explore the potential of markers like CAR and SII in detecting low-grade inflammation, and further probe into the role of sleep, nutrition, and physical activity, emphasising the paramount role of comprehensive hospital care.